2016
DOI: 10.1007/s12035-016-9968-1
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Linoleic Acid Lowering Reduces Lipopolysaccharide-Induced Increase in Brain Arachidonic Acid Metabolism

Abstract: Linoleic acid (LA, 18:2n-6) is a precursor to arachidonic acid (AA, 20:4n-6), which can be converted by brain lipoxygenase and cyclooxygenase (COX) enzymes into various lipid mediators involved in the regulation of brain immunity. Brain AA metabolism is activated in rodents by the bacterial endotoxin, lipopolysaccharide (LPS). This study tested the hypothesis that dietary LA lowering, which limits plasma supply of AA to the brain, reduces LPS-induced upregulation in brain AA metabolism. Male Fischer CDF344 rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
28
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 64 publications
3
28
1
Order By: Relevance
“…In response to LPS, n-3 LC-PUFA-supplemented mice display an anti-inflammatory SPM profile whereas n-3 LC-PUFA-deficient mice exhibit a pro-inflammatory SPM profile [69]. These results corroborate previous ones in vivo [171][172][173][174][175][176] and in vitro in macrophages [177,178] and microglia [179][180][181].…”
Section: Nutrition As a Factor Of Variation Of Spm Levelssupporting
confidence: 86%
“…In response to LPS, n-3 LC-PUFA-supplemented mice display an anti-inflammatory SPM profile whereas n-3 LC-PUFA-deficient mice exhibit a pro-inflammatory SPM profile [69]. These results corroborate previous ones in vivo [171][172][173][174][175][176] and in vitro in macrophages [177,178] and microglia [179][180][181].…”
Section: Nutrition As a Factor Of Variation Of Spm Levelssupporting
confidence: 86%
“…Because only extreme differences in LA intake have previously been documented to alter a small number of tissue AA oxylipins (4,14,15,33), and because there is strong evidence that dietary LA does not alter blood AA levels (16), it has been concluded that dietary LA has minimal effects on AA oxylipins. The current findings, however, demonstrate that increased dietary LA within the usual dietary range resulted in higher levels of 10-12 AA oxylipins in kidney and liver, as well as many LA, GLA, EDA, DGLA, and AdA oxylipins in these tissues, and LA oxylipins in serum.…”
Section: Discussionmentioning
confidence: 99%
“…These oxygenated because a higher n-6/n-3 PUFA ratio is thought to increase inflammation via its effect on altering the n-6/n-3 oxylipin profile (11)(12)(13). However, although it has recently been shown that large changes in LA alter the levels of LA oxylipins (4,14,15), whether changes in dietary LA in the normal range of current intake affect LA oxylipins is not known. The effect of dietary LA on LA oxylipins is also likely important because LA oxylipins can make up more than half of all oxylipins by mass (e.g., rat kidney) (4).…”
mentioning
confidence: 99%
“…Recent work highlighted that dietary supplementation with n-3 PUFAs and antioxidants dramatically increases Ab phagocytosis by monocytes (Fiala et al, 2015). As discussed before, increasing DHA levels via dietary means or genetic approaches potently reduces brain proinflammatory cytokine production in animal models of acute and chronic inflammation (Orr et al, 2013;Delpech et al, 2015a,b;Taha et al, 2017), aging (Labrousse et al, 2012;Moranis et al, 2012), or AD (Casali et al, 2015;Hopperton et al, 2016). Concomitantly, DHA potently promotes microglia phagocytic activity (Chen et al, 2014), including toward Ab in vitro (Hjorth et al, 2013).…”
Section: A Lc-pufa Dietary Interventions To Limit Neuroinflammationmentioning
confidence: 98%